Analyzing emergency evacuation scenarios in Ghana based on different groups profiles in a classroom. Issue 1 (31st December 2023) - Bilintoh, Nashiru Mumuni Daniel; Zhang, Jun; Karim, Rehmat; Rafaqat, Warda
Abstract: It depends on both the pedestrians and the building whether they can be evacuated from a building safely and quickly in any situation. Understanding pedestrian behavior is crucial when designing buildings for safe evacuation in emergencies like earthquakes and fires. Since this topic has yet to be fully explored in Ghana, we conducted experiments in a classroom to capture the characteristics of pedestrian movements during an emergency. In this experimental study, students were asked to pretend to evacuate during an emergency. The simulation and comparison of the evacuation of students from a classroom were conducted using a multi-grid model in our study. The study examines several factors that influence evacuation characteristics. These factors include pedestrian density, speed, time, door width, body mass index, and classroom capacity. The paper describes in detail all study phases, including planning, preliminary work, observational studies, empirical data collection, and statistical analysis. It thoroughly examines pre-movement time, group density, and velocities for groups and individuals moving through doorways, traveling distances, and walking in educational settings. A person's state of mind and psychological abilities are also taken into account, as well as their level of emotional involvement in the movement. The obtained results are also discussed for evacuation planning in educational institutions under different conditions.